Consórcio girassol x feijão-de-corda e girassol x amendoim em série de substituição - Rodrigues, Clécio da Frota (2011)
The cultural intercrop is about sowing two or more species in the same area, in a way that one of the species manages to live by the other during all or at least part of its cycle. The aim of this paper is to evaluate the grain and pod production and their components, the sunflower cultures cv. CATISSOL with cowpea cv. “Setentão” and peanut cv. PI 165 317, belonging to the ‘Spanish’ group intercropped in replacing series. The study was developed from April to July, 2010, in a farm named “Lavoura Seca”, located in Quixadá, Ceará, Brazil. The research profile was the one in random blocks of 9 treatments. For the sunflower studies, it was used 7 treatments and 4 repetitions, whereas for the cowpea and peanut study, it was used 4 treatments and 4 repetitions. For the monocultures, the portions were made of 6 five-meter rows, whereas for the intercropped cultures, th e portions were made of 12 five-meter rows.The treatments were about the monoculture of sunflower (GI100%), cowpea (FE100%), peanut (AM100%) and intercrop between these cultures where the plant populations varied in the following proportions: GI75% + FE25%; GI50% + FE50%; GI25% + FE75%; GI75% + AM25%: GI50% + AM50%; GI25% + AM75%. The monoculture results were superior to the intercropped ones. For the intercrop of cowpea, the biggest productivity of sunflower achenes happened in the association 75% sunflower + 25% cowpea. For the intercrop between sunflower and peanut, the peanut presence in the proportion of 25% plant population did not affect the result productivity of sunflower achenes in relation to the monoculture. The components of peanut production, pod number, pod weight, amount of seeds for each pod, seed weight for each pod, and the weight of 100 seeds, were not affected by different proportions of peanut and sunflower intercrop. The intercropped systems showed the Land Efficient Use superior to 1 (one) in the plant population proportion GI75%+FE25%, GI50%+FE50%, GI75%+AM25% e GI25%+AM75%, meaning that different intercropped arrangements are more advantageous than monocultures.